2021
DOI: 10.1002/anie.202113266
|View full text |Cite
|
Sign up to set email alerts
|

Reactivities of Interstitial Hydrides in a Cu11 Template: En Route to Bimetallic Clusters

Abstract: In sharp contrast to surface hydrides,r eactivities of interstitial hydrides are difficult to explore.W hen treated with am etal ion (Cu + ,A g + ,a nd Au + ), the stable Cu I dihydride template [Cu 11 H 2 {S 2 P(O i Pr) 2 } 6 (C CPh) 3 ]( H 2 Cu 11 )g enerates surprisingly three very different compounds,n amely [CuH 2 Cu 11 {S 2 P(O i Pr) 2 } 6 (C CPh) 3 ] + (1), [AgH 2 Cu 14 {S 2 P-(O i Pr) 2 } 6 ((CCPh) 6 ] + (2), and [AuCu 11 {S 2 P(O i Pr) 2 } 6 (C CPh) 3 Cl] (3). Compounds 1 and 2 are both M I species an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 56 publications
0
16
0
Order By: Relevance
“…Compounds 1 and 2 were investigated by DFT calculations at the BP86/Def2-TZVP level of calculations (see Computational Details in the Supporting Information). For the sake of computational limitations, the dtp and dsep ligands were replaced by S 2 PH 2 and Se 2 PH 2 models, respectively, a simplification which has been proved to be reasonable in many past investigations. ,,,,, For each ligand, both C 1 and C 3 structures were considered. The resulting computed models are labeled 1′ ( C 1 ), 1′ ( C 3 ), 2′ ( C 1 ), and 2′ ( C 3 ) in the following.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Compounds 1 and 2 were investigated by DFT calculations at the BP86/Def2-TZVP level of calculations (see Computational Details in the Supporting Information). For the sake of computational limitations, the dtp and dsep ligands were replaced by S 2 PH 2 and Se 2 PH 2 models, respectively, a simplification which has been proved to be reasonable in many past investigations. ,,,,, For each ligand, both C 1 and C 3 structures were considered. The resulting computed models are labeled 1′ ( C 1 ), 1′ ( C 3 ), 2′ ( C 1 ), and 2′ ( C 3 ) in the following.…”
Section: Resultsmentioning
confidence: 99%
“…18−20 Examples are explicitly demonstrated on the two encapsulated hydrides of [Cu 11 H 2 (dtp) 6 (C 2 Ph) 3 ]. 20,21 In addition, an interstitial hydride connected to noble metals, whose electronegativity values are larger than that of H, can behave as a "metallic" hydrogen. 8−13 Tsukuda and co-workers reported that the hydride dopant in (PdH@Au 10 ) 3+ contributes to the cluster eight-electron count, (1S) 2 (1P) 6 .…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For M=Cu or Ag, the hydrides behave as regular 2-electron ligands, but for M=Au, they behave as electron donors, leading to the formation of a 2-electron superatom, with liberation of H 2 . [47] The neutron diffraction study proved that the trigonal pyramidal hydrides (μ 4 -H in AgCu…”
Section: Hydrides In Copper Nanoclusters To Form Stable Superatomsmentioning
confidence: 95%
“…[46] 3 Cl], see Figure 2. [47] The Cu + and Ag + treated clusters remain both M(I) species and maintain the Werner E. van Zyl is Professor of Chemistry at the University of KwaZulu-Natal, South Africa. He received BScHons and MSc degrees in South Africa, and a PhD degree (1998) in inorganic chemistry from Texas A&M University, USA, followed by postdoctoral work (1999)(2000)(2001)(2002)(2003) same number of hydride ligands as the precursor, but the Au + treated cluster has no hydride and exhibits a mixed-valent [AuCu 11 ] 10 + metal core, making it a 2-electron superatom.…”
Section: Hydrides In Copper Nanoclusters To Form Stable Superatomsmentioning
confidence: 99%